Synthesis and application of magnetic PS@Fe3O4 microparticles for improving nitrogen removal in wastewater treatment process. Issue 4 (August 2022) - Chen, Ying; Zhang, Fengyuan; Shi, Xiaoshuang; Lu, Mingyi; Qin, Kang; Feng, Quan; Guo, Rongbo
Abstract: This paper aims to improve the biological nitrogen removal performance by using magnetic polystyrene composite microparticles (PS@Fe3 O4 ). Three types of PS@Fe3 O4 with different surface morphologies were prepared by in-situ emulsion polymerization. Then, the optimum was creatively used as a biofilm carrier to form magnetic activated sludge (MAS) in lab-scale reactors. Compared to the conventional activated sludge, the utilization of PS@Fe3 O4 accelerated the sludge settling velocity to 0.76 m/h. In addition, the ammonium nitrogen removal, total nitrogen removal and simultaneous nitrification and denitrification improved by 7.08%, 24.27% and 19.53%, respectively. The dissolved oxygen concentration and pH were observed to reveal the effect of PS@Fe3 O4 on the nitrogen removal process. Based on microbial community analysis, there were more nitrifying and denitrifying bacteria in the MAS. Therefore, the novel developed PS@Fe3 O4 can be a promising utilization material as a biofilm carrier for biological wastewater treatment. Graphical Abstract: ga1 Highlights: Rough PS@Fe3 O4 microparticles were creatively used as biofilm carriers. Developed carriers had effects on sludge settling velocity under magnetic field. Developed carriers could enhance NH4 + -N, TN removal and SND performance. More nitrification and denitrification bacteria existed in the MAS than CAS.